Novel mandibular gland volatiles from Apterostigma ants. (June 2017) - Hogan, Conor T.; Jones, Tappey H.; Zhukova, Mariya; Sosa-Calvo, Jeffrey; Adams, Rachelle M.M.
Abstract: The fungus-farming ants are a well-studied evolutionary radiation within the subfamily Myrmicinae that associate with a web of symbionts that span kingdoms. Members of the Apterostigma pilosum species group cultivate unique basidiomycete fungi belonging to the coral-mushroom family Pterulaceae, a family of fungi that is distantly related to the Agaricaceae ( Leucoagaricus and Leucocoprinus ) fungi grown by most fungus-farmers including other members in the genus Apterostigma ( A. auriculatum group and A. megacephala ). A chemical analysis using gas chromatography–mass spectroscopy of the mandibular gland volatiles of two species – A. dentigerum and A. manni – revealed the presence of an extraordinary diversity of natural products. Many of these compounds are new to Arthropoda, such as a homologous series of 3-methyl-2-alkanones, 2-methyl-2-alkenals, and 1-phenyl-2-propanone in A. dentigerum and 1-phenyl-2-propanol in A. manni. These results identify a remarkable divergence of compounds across the fungus-growing ants and other members in Myrmicinae. Functions of these natural products are proposed and discussed. Highlights: Apterostigma dentigerum and A. manni have a novel array of ant mandibular compounds. A. dentigerum has a series of unsaturated aldehydes new to Arthropoda. Aldehydes also found in lemon-peel extract were identified in A. dentigerum ants. Three 3-methyl-2-alkanones, known only from Bengal tiger urine, were found.